Digital Culture –A Hurdle or A Catalyst in Employee Engagement - Ms. Yuvika Singh; Dr. Heena Atwal (International Journal of Management Studies (IJMS), 2021)
Employee engagement plays a very important role in an organization when it is desired for high productivity, high quality services and speedy strategic improvement, keeping in mind the company’s role and performance. In this 21st century the technology plays a very important role in order to collaborate the preferences and roles of an organization with those of the employees working within the organization, so that mutual goals can be achieved in an effective and efficient manner. This can be achieved by encouraging a work environment which uses different technological and cultural factors allowing its employees to succeed. In order to create an enriching employee experience, effective strategies need to get started right from new joiners to the conduction of exit interviews, which are often ignored by many organizations. HR managers need to focus on beyond its traditional role of handling different areas under employee engagement separately. Although the understanding of these areas may include monetary and non-monetary rewards, employee benefits, conducive environment and learning atmosphere which greatly requires a digital framework where all of these factors may converge. Although artificial intelligence, automation and other higher digital technologies also create a feeling of insecurity among the employees. This paper throws some light on the issue that how the technology or the culture leads to the real digital transformation and contributes towards employee engagement.